2020
DOI: 10.1186/s12884-020-02938-4
|View full text |Cite
|
Sign up to set email alerts
|

High dose and low dose oxytocin regimens as determinants of successful labor induction: a multicenter comparative study

Abstract: Background Induction of labor by Oxytocin is a routine obstetric procedure. However, little is known regarding the optimal dose of oxytocin so as to bring successful induction. This study was aimed at comparing the effects of high dose versus low dose oxytocin regimens on success of labor induction. Methods Hospital-based comparative cross-sectional study was conducted in four selected hospitals in Ethiopia prospectively from October 1, 2017 to May 30, 2018. A total of 216 pregnant women who undergo induction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
(34 reference statements)
1
11
0
Order By: Relevance
“…It was found that oxytocin regimen didn’t show significant association with induction success and adverse maternal outcome in another article of the same project unlike adverse perinatal outcome that increase with high dose oxytocin [ 13 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was found that oxytocin regimen didn’t show significant association with induction success and adverse maternal outcome in another article of the same project unlike adverse perinatal outcome that increase with high dose oxytocin [ 13 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arbaminch general hospital has 1500 births per year, Kuyu general hospital about 1350 births per year and Shenen gibe general hospital has nearly 1400 births per year. The methodology used in the current study is similar to that of another study related to the same project which has been published in BMC Pregnancy and Childbirth [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…If a woman gave birth vaginally with or without the aid of an instrument after labor induction ( 31 ).…”
Section: Methodsmentioning
confidence: 99%